2018
DOI: 10.1063/1.5018020
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous compression behaviour in Nd2O3 studied by x-ray diffraction and Raman spectroscopy

Abstract: The structural stability of hexagonal Nd2O3 under pressure has been investigated by in situ synchrotron angle dispersive x-ray diffraction and Raman spectroscopy up to 53.1 GPa and 37.0 GPa, respectively. Rietveld analysis of the x-ray diffraction data indicate that the hexagonal Nd2O3 undergoes an isostructural phase transition in the pressure range from 10.2 to 20.3 GPa, accompanied by anomalous lattice compressibility and pressure-volume curve. A third-order Birch-Murnaghan fit based on the observed Pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…A-type Nd 2 O 3 has been observed to suffer a reversible PT above 27 GPa towards a monoclinic s.g. P2/m phase [67]. However, other work has suggested a 1st-order isostructural PT above 10 GPa [68]. This behavior is in contrast with that of Ce 2 O 3 , which seems to be stable in the A-type phase up to 70 GPa.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…A-type Nd 2 O 3 has been observed to suffer a reversible PT above 27 GPa towards a monoclinic s.g. P2/m phase [67]. However, other work has suggested a 1st-order isostructural PT above 10 GPa [68]. This behavior is in contrast with that of Ce 2 O 3 , which seems to be stable in the A-type phase up to 70 GPa.…”
Section: Introductionmentioning
confidence: 78%
“…Finally, as regards the B→A PT, the pressure of the transition once again increases along the lanthanide series with the increase in atomic number or the decrease in the ionic radius. As observed, no experimental data for the B→A PT 4.0 XRD N2, Ar [11] 4.2 2.5 XRD Silicon Oil [45] The HP behavior of A-type compounds has been studied in Nd2O3 [67,68], Ce2O3 [69], and La2O3 [11]. A-type Nd2O3 has been observed to suffer a reversible PT above 27 GPa towards a monoclinic s.g. P2/m phase [67].…”
Section: Compmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there is no Raman spectroscopy data for the trigonal structure of Eu 2 O 3 , but the Raman modes measured for other A-type sesquioxides are arranged just as in our calculations: two bending vibrations of low-frequency between 100 and 200 cm –1 and two stretching vibrations occurring at a higher frequency region between 400 and 450 cm –1 . 9 , 30 , 31 Under pressure, the Raman modes of the trigonal structure shift to higher frequencies. In Table 1 , the frequencies of the zone-center modes calculated for the trigonal structure at p = 0 and 6 GPa are presented.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…This signifies that, the monoclinic phase is completely transformed to the hexagonal structure well below this pressure. Also, it has been observed that, the 100 peak of the hexagonal structure of and 0.6 hardly shift with an increase of pressure in the ~ 10–22 GPa pressure regime, indicative of the presence of anomalous lattice compressibility, similar to the one in the hexagonal structure of pristine La 2 O 3 , Nd 2 O 3 and Eu 2 O 3 15 , 17 , 18 .
Figure 1 HPXRD pattern of x = 0.3–0.6 representing the high pressure behavior of (Eu 1− x La x ) 2 O 3 .
…”
Section: Resultsmentioning
confidence: 97%